Influence of biphasic calcium phosphate surfaces coated with Enamel Matrix Derivative on vertical bone growth in an extra‐oral rabbit model. Issue 10 (22nd December 2015) - Wen, Bo; Li, Zhen; Nie, Rongrong; Liu, Chao; Zhang, Peng; Miron, Richard J.; Dard, Michel M.
Abstract: Objective: The aim of this study was to investigate the ability of Enamel Matrix Derivative (EMD) on vertical bone regeneration around dental implants placed in an extra‐oral rabbit model. Material and methods: A total of 30 Straumann BL implants were partially embedded in transverse orientation into the posterior mandibles of 15 rabbits. Macro‐structuring BiPhasicCaPST (BCPT1), micro‐structuring BiPhasicCaPST (BCPT2), and deproteinized bovine bone mineral (DBBM) were placed around the implant and covered with a scaffold stabilizing "umbrella." EMD was incorporated within the scaffold for test sites, but not control sites. Histological analysis was performed on retrieved specimens after 10 weeks of healing to assess new bone formation. Results: All treatment groups displayed new supracrestal bone formation as determined by histomorphometric measurements, with mean values of new bone height ranging between 0.62 and 1.13 mm. Histological analysis revealed a higher mean bone formation (%) around the test sites where EMD (34.7, 95%CI: 27.1–39.4) was released from the scaffold, whereas the control group without EMD release (26.4, 95%CI: 16.3–31.9) ( P  = 0.069). The mean fBIC (%) in the BCPT2 group increased by the addition of EMD relative to no EMD (67.2, 95%CI: 48.6–84.1) and (54.7, 95%CI: 32.3–68.9), respectively). The BCPT2/EMD and DBBM/EMD interventions showed the greatest mean bone density (BA/TA), respectively, (12.8, 95%CI: 8.9–36.5) and (11.2, 6.3–16.4) in ROI 1. Values in ROI 2 were, similarly, (24.9, 95%CI: 17.2–31.7) and (27.7, 19.2–35.3). BA/TA in ROI 2 differences between the BCPT2 groups with and without EMD was statistically significant ( P  = 0.026), as well as the DBBM groups with and without EMD ( P  = 0.038). Conclusions: A layer of new bone was formed in both test and controls. The release of EMD from BCPT2 and DBBM adjacent to a bone‐level implant with an SLActive surface and scaffold retention umbrella consistently regenerated the greater fBIC and bone density along the length of the implant.